1996
DOI: 10.1021/jo950969j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trideca-O-methyl-α-pedunculagin. Diastereo-Favoritism Studies on Intramolecular Ester-Cyclization of Axially Chiral Diphenic Acids with Carbohydrate Core

Abstract: Total synthesis of trideca-O-methyl-alpha-pedunculagin was achieved by a simple sequence. The key step is the synthesis of methyl 4,6-O-benzylidene-2,3-O-[(S)-4,4',5,5',6,6'-hexamethoxydiphenoyl]-alpha-D-glucopyranoside through intramolecular ester-cyclization of racemic hexamethoxydiphenoyl chloride with methyl 4,6-O-benzylidene-alpha-D-glucopyranoside at the 2,3-position. The diastereoselectivity results obtained in the intramolecular cyclization of hexamethoxydiphenic acid to the carbohydrate core raises a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…To confirm the absolute configuration of compound 2 c , we also prepared it by route A. To this end, we relied on the conditions reported by Itoh et al 34a. to achieve a bis‐esterification reaction between commercially available sugar derivative 3 c and the racemic hexabenzyloxydiphenoyl chloride 4 b 24 by using 4‐dimethylaminopyridine (DMAP) in CH 2 Cl 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the absolute configuration of compound 2 c , we also prepared it by route A. To this end, we relied on the conditions reported by Itoh et al 34a. to achieve a bis‐esterification reaction between commercially available sugar derivative 3 c and the racemic hexabenzyloxydiphenoyl chloride 4 b 24 by using 4‐dimethylaminopyridine (DMAP) in CH 2 Cl 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Nelson oxazoline-mediated asymmetric Ullmann coupling (Scheme 17.12) [50]. The results were applied to the synthesis of a permethyl derivative (61) of pedunculagin [2,3-; 4,6-bis-(S)-HHDP glucose] [53]. Itoh et al demonstrated diastereoselective esterification of racemic biaryl acid chloride 57 with a 2,3-diol of the glucose derivative (58) [52].…”
Section: Synthesis Of Ellagitannins By Double Esterification Of Hexahmentioning
confidence: 99%
“…True polyphenols from tannin and other WBSSH types are consistently biosynthesized in the natural sources where they derive; their chemical syntheses (with standard bench organic chemical methods) were to some extent limited until first decade of the new millennium due to these syntheses involve challenging stereoselectivity and regioselectivity issues (38). Early work focused on achiral synthesis of phenolic-related constituents of polyphenols in the late 1970's, and the Nelson & Meyers synthesis of permethyled derivative of the ubiquitous and abundant diphenic acid core of the ellagitannins in 1994 (39) followed by the stereoselective synthesis of the more complex permethylated structures such as Itoh and coworker's synthesis of permethylated pedunculagin with specific attention to the axial symmetry issues in 1996, and Lipshutz and coworkers' (+)-tellimagrandin II derivative in 1994 (40). The total synthesis of a completely unmasked polyphenol that of ellagitannin tellimagrandin I, was diastereoselective sequence reported by Feldman et al (41).…”
Section: Chemical Synthesis Of Polyphenolsmentioning
confidence: 99%